Some Curvature Properties of -Manifolds - Mehmet Atçeken (Abstract and Applied Analysis)
The object of the present paper is to study -manifolds with vanishing quasi-conformal curvature tensor. -manifolds satisfying Ricci-symmetric condition are also characterized.